STRUCTURAL EQUATION MODELLING (SEM) PENGGUNAAN SEM – GSCA DAN APLIKASI GSCA – PRO UNTUK MAHASISWA DAN DOSEN - Teguh Iman Santoso; Muhammad Rozali; Riri Hanifa (Pusat Riset dan Inovasi Nasional, 2022)
The Tri Dharma of Higher Education requires lecturers to carry out research, teaching and community service. Therefore as a form of lecturer's moral responsibility to the community to improve knowledge through formal and non-formal education. Our team of lecturers will carry out community service in the form of making training on the internet in the form of webminars that are very suitable to reach audiences during this pandemic. The coaching material that will be delivered by the lecturer team includes the use of SEM-GSCA and the GSCA-PRO application for research for students and lecturers (S1, S2, S3). The purpose of this training is to introduce SEM (Structural Equation Modeling) Applications Generalized Structure Component Analyst and how to use and process data through the GSCA-PRO application. So far, students and lecturers are still patterned with a regression analysis, by studying SEM students and lecturers will have the freedom in making the research model. The benefit that can be taken from training on the use of SEM-GSCA and the GSCA-PRO Application for research for students and lecturers is that there are other options offered to students and lecturers in terms of doing research.